The Construction of Sustainable Palm Oil Image In Naga Naga Naga Film - Mochamad Husni; Frengki Napitupulu (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
The focal subject of examination is a film that portrays the establishment of palm oil plantations, while the use of Berger-Luckmann's social construction theory serves as two key factors that emphasize the importance of this research. The film "Naga Naga Naga" narrates the tale of Nagabonar's granddaughter, who encounters educational difficulties. This research employs a descriptive-qualitative approach to elucidate the concurrent processes and dialectics of externalization, objectivation, and internalization. The researcher gathered data by conducting observations of the Naga Naga Naga film in theaters and evaluating various sequences using a subscription-based streaming platform. By employing Charles S. Peirce's semiotic approach to analyze, the finding showed that not just the underlying motivations behind the signs and meanings associated with the implementation of sustainability principles, such as environmental harmony and community care, but also identifies components of "artistic and logical narrative" that impact the process of constructing a mental representation of palm oil farms. These findings are highly valuable for formulating campaign strategies that utilize films to shape public awareness.